Utilization of saba banana (musa paradisiaca L.) peel for fiber content improvement in beef burger patty - Reyes, Marnelle R.; Rumbaoa, Rowena Grace O. (2010)
ABSTRACT This study aimed to utilize Saba banana peel (BP) in beef burger patty. The optimum level of substitution was established at 55%. Using 50 randomly selected untrained panelists, sensory results revealed juiciness and tenderness ratings to be more favored with BP-substituted beef patty than control. A lesser burger flavor and darker color, however, were observed with substitution. Despite the fair acceptability in color and burger flavor ratings, the overall acceptability of the product was not significantly different among formulations rendering a satisfactory score. Lightness, redness, and yellowness (as measured by L*, a*, b* values) decreased significantly in BP-substituted beef patties while improvement or retention on some physico-chemical properties (WHC, cooking loss, pH) was observed. The process and formulation for the optimum substitution level was further standardized. Three runs of 55%-BP substituted patties were manufactured. The BP-substituted patties revealed 6% increase in product yield and decreased cost by 48.5% compared with the control. Microbial growth was observed to be relatively lower in BP-substituted beef patties than in control. The substituted beef patty obtained the following chemical results: 39.42% moisture content, 16.8% crude fat, 6.9% ash, and 5.32% crude fiber. However, the amount of fiber concluded in this study was delimited to celluloses and some lignin as a rough estimate to the total dietary fiber constituents found in banana peel. Nonetheless, BP substitution was able to increase the crude fiber content of beef burger patty by ~500%.
Thesis (BSFT)--University of the Philippines, Diliman
Keywords: Bananas; Hamburgers; Food--fiber content